Improvement of Sinter Quality for the ISP - Kikuta K (The Australasian Institute of Mining and Metallurgy, 1993)
ISP (Imperial Smelting Process) produces zinc and lead simultaneously from zinc and lead sulphide concentrates and recovers copper and precious metals into a lead bullion. The strength of sinter is important to keep permeability in the shaft of the Imperial Smleting Furnace. The residual sulphur content of the sinter is also important as it causes metal losses into slag. The paper describes an investigation into the sintering operations to improve sulphur elimination and sinter strength. The micro structure of the sinter and the effect of the blast rate, sintering temperature etc have been studied.